Pembuatan Biodiesel Dari Minyak Nyamplung Dengan Menggunakan Katalis Basa Na2SiO3/Fe3O4 - Nissa Aqhilla; Edy Saputra; Ahmad Fadli (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Biodiesel is an alternative energy to replace fossil fuels. It can be made by transesterification process of vegetable oils. During the process of making biodiesel usually was used NaOH or KOH as homogeneous catalyst which has the disadvantage the formation of side products such as soaps and complexity of the separation of catalyst. Therefore, in this study Na2SiO3/Fe3O4 catalyst is used. The independent variables of this research are mol ratio of CIO and methanol 1:6, 1:8, 1:10 and loading catalyst Na2SiO3/Fe3O4 1%, 2%, 3%. Density (40°C) of biodiesel is 876,18 kg/m3, kinematic viscosity (40°C) is 4,63 cSt, flash point is 107°C, and acid value is 0,49 mg-KOH/g-biodiesel.Keywords: Biodiesel, Catalyst, CIO, Transesterification